1989
DOI: 10.1212/wnl.39.8.1121
|View full text |Cite
|
Sign up to set email alerts
|

Agonist substitution in advanced Parkinson's disease

Abstract: We studied whether Parkinson's disease patients who had lost efficacy from pergolide (PERG) could benefit if transferred to bromocriptine (BCT) therapy. Using paired t-tests, we compared motor scores at baseline (when patients were still on PERG) and after 6 months of BCT therapy in 11 patients. No significant improvement occurred in any measure on BCT therapy (mean dose 33.6 mg/day), although patients remained stable. In 6 patients on whom "on/off" data were obtained, decreased "off" time and increased "on" t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…In a fiveyear study of bromocriptine and pergolide, Goetz et al found that patients whose bromocriptine efficacy waned, experienced renewed efficacy after switching to pergolide [4]. Similarly, in patients showing a progressive loss of efficacy from pergolide, conversion to bromocriptine stabilized motor function [5].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a fiveyear study of bromocriptine and pergolide, Goetz et al found that patients whose bromocriptine efficacy waned, experienced renewed efficacy after switching to pergolide [4]. Similarly, in patients showing a progressive loss of efficacy from pergolide, conversion to bromocriptine stabilized motor function [5].…”
Section: Discussionmentioning
confidence: 99%
“…■ Key words dopamine agonists · pramipexole · Parkinson's disease · motor complications dopamine agonists are quite similar [12,18], a few studies indicate that in patients in whom efficacy waned from one dopamine agonist, renewed benefit may occur after switchover to another dopamine agonist [4,5]. This has been documented in patients switched from bromocriptine to pergolide [4] and vice versa [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, switching from bromocriptine to pergolide or pergolide to bromocriptine may provide such benefit. 28,29 Moreover, DAs with different elimination pathways should be considered if patients have liver and/or kidney disease. If patients have concomitant liver disease, pramipexole is more appropriate because it is not metabolized by the liver and is excreted mostly via the kidney.…”
Section: Dopamine Receptor Agonistsmentioning
confidence: 99%
“…We documented comorbidities, disease duration and medication dosages at last visit. For dopamine agonists, a pergolide equivalent dosage was calculated as 1 mg of pergolide ¼ 1 mg of pramipexole ¼ 3 mg of ropinirole ¼ 10 mg of bromocriptine (Goetz et al, 1989). The Institutional Review Board (IRB) of the Rush University Medical Center approved the study, and participants signed informed consent.…”
Section: Diagnostic Scoring Of Psp and Cbdmentioning
confidence: 99%